2019
DOI: 10.1111/ecot.12234
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental regulation on Chinese spatial development

Abstract: We examine the relationship between environmental regulation and spatial development in China. Exploiting changes in national pollution standards for three industries, ammonia, paper and cement, we measure the impact of environmental regulation on industry productivity. Our results suggest that national pollution standards do not affect industry productivity, but they reallocate productivity spatially. We show that regulated industries located in developing cities increase their productivity compared to simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…On the other hand, environmental regulation will promote the increase of GTFP by increasing research and development, that is, the "innovation compensation" effect. For example, Naso et al [60] believe that the increase in the intensity of environmental regulations in cities will "force" enterprises to increase R&D and innovation in terms of factor input, energy consumption, energy conservation, and emission reduction, so as to improve their competitiveness to compensate. e negative impact is caused by the increase in environmental governance costs, which in turn promotes the improvement of urban GTFP [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, environmental regulation will promote the increase of GTFP by increasing research and development, that is, the "innovation compensation" effect. For example, Naso et al [60] believe that the increase in the intensity of environmental regulations in cities will "force" enterprises to increase R&D and innovation in terms of factor input, energy consumption, energy conservation, and emission reduction, so as to improve their competitiveness to compensate. e negative impact is caused by the increase in environmental governance costs, which in turn promotes the improvement of urban GTFP [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…The government can implement FER through policies such as collecting environmental taxes and setting emission standards as a way to reduce production inputs of enterprises and thus reduce pollution emissions (Chen andZhang 2012, M Greenstone et al 2012). IER can also be measured by input indicators such as pollution discharge fees, environmental protection related financial expenditure and environmental pollution control investment (Testa et al 2014, Naso et al 2017. Fredriksson and Millimet (2002) analyzed the strategic interaction and environmental policy formulation of each state in the United States, measured and formulated standards with formal environmental regulation cost input indicators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has also been claimed that environmental regulation can promote regional technological innovation, offset the cost of environmental governance, and then improve GTFP [ 21 , 22 , 23 ]. Naso et al [ 24 ] reported that the enhancement of environmental regulation intensity would “force” enterprises to increase research and development (R&D) in terms of energy consumption and emission reduction. In this way, the competitiveness of enterprises could be improved to promote the urban GTFP [ 25 , 26 , 27 ].…”
Section: Background and Introductionmentioning
confidence: 99%